(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The article shows the results of obtaining a hemosorbent of carbon material. Samples of a hemosorbent of a multichannel cellular structure were prepared, obtained under various modes of processing the mass and the ratio of components. Data on adsorption activity for methylene blue were obtained. A preclinical study was conducted on animals according to the indicators of the general blood test.